India's FTAs with East and SE Asia : impact of India-Malaysia CECA on the edible oil value chain - Nilanjan Ghosh; Avishek Konar; Sriparna Pathak (India's FTAs with East and SE Asia : impact of India-Malaysia CECA on the edible oil value chain, 2015)
This paper formulates an analytical framework to assess the impacts of India's Free Trade Agreements (FTAs) on commodity value chains. Existing academic literature have relied on examining Balance of Payments (BoP) to assess the impact of FTAs. This paper views such methodology as reductionist, and instead offers alternative lenses of the impacts on the commodity value chain. This paper brings into fold the concerns for the wellbeing of various stakeholders in the value chain. Using an economic model, this study analyses the impact of tariff changes on the well-being of consumers through consumer surplus, processors through producer surplus, labour through wage-bill, farmers through farmers' surplus, and government through revenue generated. The sum of the changes of all the above is considered, and the change in total social surplus from the change in the tariff regimes is examined. The paper presents a best possible scenario of a five-percent decline in tariff from the 2010-11 base case, with minimum harm causing the various stakeholders.
842177647